2010
DOI: 10.1007/jhep05(2010)043
|View full text |Cite
|
Sign up to set email alerts
|

MSSM forecast for the LHC

Abstract: Abstract:We perform a forecast of the MSSM with universal soft terms (CMSSM) for the LHC, based on an improved Bayesian analysis. We do not incorporate ad hoc measures of the fine-tuning to penalize unnatural possibilities: such penalization arises from the Bayesian analysis itself when the experimental value of M Z is considered. This allows to scan the whole parameter space, allowing arbitrarily large soft terms. Still the low-energy region is statistically favoured (even before including dark matter or g-2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 91 publications
5
53
0
Order By: Relevance
“…space is multiplied by ∆ −1 µ , which is consistent with the above probabilistic interpretation of ∆ [45,89,91,92]. Actually, the equivalence is exact if one assumes that the prior in the parameters is factorizable, i.e.…”
Section: Jhep06(2015)070supporting
confidence: 73%
“…space is multiplied by ∆ −1 µ , which is consistent with the above probabilistic interpretation of ∆ [45,89,91,92]. Actually, the equivalence is exact if one assumes that the prior in the parameters is factorizable, i.e.…”
Section: Jhep06(2015)070supporting
confidence: 73%
“…[56] for an explicit expression for J), µ Z is the value of µ that reproduces the experimental value of M Z for the given values of {s, m 0 , m 1/2 , A 0 , B} and P (s, m, M, A, B, µ) is the prior in the initial parameters (For a detailed discussion on the chosen priors see Ref. [57]). One of the main consequences of this approach is that the results exhibit a remarkable robustness under changes of the priors (see Ref.…”
Section: Distinguishing the Mued Scenario From The Cmssm With Dirementioning
confidence: 99%
“…One of the main consequences of this approach is that the results exhibit a remarkable robustness under changes of the priors (see Ref. [57]), showing an absence of dependences on the initial chosen ranges for the CMSSM parameters. Moreover the results are compatible with likelihood based analyses [58].…”
Section: Distinguishing the Mued Scenario From The Cmssm With Dirementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this measurement already significantly constrains the parameter space of supersymmetric models. Reference [8] studied the implications of the Higgs mass measurement for the minimal supersymmetric standard model (MSSM) with five parameters (the constrained MSSM), and found that the posterior probabilities for these parameters are narrowly distributed. Reference [9] further extended the model to include the nonuniversality in gaugino and Higgs masses, and found qualitatively similar results.…”
Section: Introductionmentioning
confidence: 99%